The impact of the Dieselgate vehicle emmissions scandal on customer equity in the South African automotive industry - Pillay, Sylvester Deenan (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
Prominent German automotive manufacturers had been tampering with emissions for some time before it became public knowledge in September 2015. It is then that that the term 'Dieselgate' was coined in reference to the scandal. As the scandal became public knowledge, manufacturers accused of emissions cheating faced challenges on several fronts, including legal, financial and environmental. While the 'backlash' as a result of the scandal was apparent in other countries, it was not as apparent in South Africa. This research paper set out to explore the impact that the Dieselgate scandal had in South Africa in terms of customer equity. Data analysis was undertaken using a two-pronged approach. The first of these was analysis of vehicle sales data using a paired t-test. This was to understand whether sales had seen a decline pre-, as well as post-scandal. The results point to a sales decline, this highlights that Dieselgate was a factor even though other, unexamined factors, were not investigated. The second instrument used was a customer equity questionnaire, this provided insight into the real opinions of consumers in South Africa about the affected brands. The analysis revealed that the affected manufacturers operating in South Africa had seen no negative effects in terms of customer equity. Based on the results, it could be said that market factors, which was not part of the research, play a great role in consumers' preferences or mindsets. Additionally, manufacturers can operate with a degree of latitude in certain markets. This is based on market factors in a specific market as well as the regulations imposed and enforced in that market. Lastly, customer equity is a complex theory that includes a multitude of converging theories. Based on this fact, it is currently difficult to evaluate customer equity in its entirety in a single paper. A comprehensive model is yet to be developed that can effectively measure customer equity in an all-encompassing way.
Keywords: Automobile industry and trade -- Germany; Automobile industry and trade -- Law and legislation -- Germany; Automobile industry and trade -- South Africa; Automobiles -- Motors -- Exhaust gas; Brand choice -- South Africa; Customer preferences -- South Africa; Consumer satisfaction -- South Africa; Brand loyalty -- South Africa; Consumer behavior -- South Africa; Dieselgate